Intravenous salbutamol in management of status asthmaticus. - Fitchett, D H (1975)
After the administration of intravenous salbutamol (100-300 mug) to 11 patients admitted to hospital with a severe exacerbation of asthma there was a mean increase in peak expiratory flow of 44% accompanied by a rise in pulse rate of 24 beats/min. Blood gas tensions showed a trend to improvement and there were no serious side effects. It is concluded that intravenous salbutamol is an effective and apparently safe bronchodilator in the management of acutely ill patients with severe asthma.